Analisis Model Co-Production (Elinor Ostrom) dalam Pengelolaan Fasilitas Publik di Taman TVRI Kota Palembang - Elivia Pasma Putri; Ade Maulidya (Yayasan Literasi Sains Indonesia, 2025)
POM IX Public Park (TVRI Park) in Palembang City is a public green open space that can be accessed for free with sports facilities, children's play areas, and gazebos. But, public facilities used to face serious problems related to maintenance, cleanliness, security, and accessibility for people with disabilities. This study uses a simple quantitative Community Satisfaction Survey (SKM) method with a Likert scale of 1–4 to a number of respondents with certain criteria, combining primary data from a questionnaire based on Elinor Ostrom's four dimensions of co-production theory and field observations as well as secondary data with analysis of news information, social media and previous research. The results show that the facilities of TVRI Park in Palembang City are damaged and rusty, vandalism occurs and low community participation. The results of the survey with a focus on management through private contributions with CSR showed minimal response (67.8% of respondents considered there was no real role), although 71% supported the government-community joint management model. Based on the results obtained, TVRI Park requires intensive improvements and multi-party collaboration to improve comfort and sustainability. The government's role in addressing the maintenance issues of public facilities can be collaborative in supporting routine budget allocations for repairs, periodic maintenance schedules, strengthening CSR incentive policies, as well as participatory programs such as monthly mutual cooperation, planning meetings, and awards for active communities to realize ideal co-production that is inclusive and sustainable.